REASSESSING HADITH AUTHENTICITY: G.H.A. Juynboll’s Common Link Theory and the Integration of Historical Criticism with Sanad Theory - Kasanah, Uswatun; Rozi, Fahrul; Aprilia, Try Heni (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
The authenticity of hadith has long occupied a central position in Islamic studies, as it determines the authority of prophetic traditions as the second primary source of Islamic law after the Qur’an. This study examines the validity of hadith through the perspective of G.H.A. Juynboll’s common link theory, which challenges the traditional assumption of uninterrupted transmission by proposing that each hadith can be traced to a single transmitter who serves as the historical nucleus of its dissemination. Employing a qualitative descriptive-analytical approach, the research draws upon Juynboll’s major works and relevant studies by both Western and Muslim scholars. Through a systematic reconstruction of transmission networks and a comparison with the classical methodology of al-jarh wa al-ta’dil, the findings demonstrate that although Juynboll’s theory offers a significant contribution to historical source criticism, it tends to interpret hadith primarily as historical constructs, thereby overlooking their theological and epistemological dimensions within the Islamic tradition. Comparative analysis with the works of Harald Motzki further indicates that hadiths associated with common links may still exhibit textual and isnad coherence extending to the Prophet’s era. The study contributes to contemporary hadith scholarship by proposing a balanced framework that integrates modern historical criticism with classical Islamic epistemology, positioning the common link theory as a complementary analytical instrument rather than a definitive criterion for determining hadith authenticity. This approach highlights the possibility of constructive dialogue between Western critical methodologies and traditional Muslim hadith sciences in the evaluation of prophetic traditions. Keotentikan hadis telah lama menjadi isu sentral dalam studi Islam karena menentukan otoritas tradisi kenabian sebagai sumber hukum Islam kedua setelah Al-Qur’an. Penelitian ini bertujuan untuk mengkaji validitas hadis melalui perspektif teori common link G.H.A. Juynboll, yang menantang asumsi tradisional mengenai kesinambungan transmisi dengan mengemukakan bahwa setiap hadis dapat ditelusuri kepada seorang perawi tertentu yang berfungsi sebagai pusat historis penyebarannya. Penelitian ini menggunakan pendekatan kualitatif deskriptif-analitis dengan memanfaatkan karya-karya utama Juynboll serta berbagai kajian yang relevan dari sarjana Barat maupun Muslim. Melalui rekonstruksi sistematis terhadap jaringan transmisi dan perbandingan dengan metodologi klasik al-jarh wa al-ta’dil, hasil penelitian menunjukkan bahwa meskipun teori common link memberikan kontribusi penting bagi kritik sumber historis, teori tersebut cenderung memandang hadis semata-mata sebagai konstruksi sejarah sehingga kurang memperhatikan dimensi teologis dan epistemologis yang melekat dalam tradisi Islam. Analisis komparatif dengan pemikiran Harald Motzki lebih lanjut memperlihatkan bahwa hadis-hadis yang dikaitkan dengan common link masih dapat menunjukkan koherensi tekstual dan sanad yang menelusur hingga masa Nabi. Penelitian ini memberikan kontribusi bagi kajian hadis kontemporer dengan menawarkan kerangka yang seimbang antara kritik historis modern dan epistemologi klasik Islam, dengan menempatkan teori common link sebagai instrumen analitis yang bersifat komplementer, bukan sebagai standar final dalam menentukan autentisitas hadis. Dengan demikian, penelitian ini menegaskan adanya kemungkinan dialog yang konstruktif antara metodologi kritis Barat dan ilmu hadis tradisional dalam mengevaluasi tradisi kenabian.